(3YHQI GddHjH HeUQY GdcFjHs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3Ydi efhGd QSGdI JMJhj Ydi GdefXhe hGdefKhQ, hJJCQLM fhGaMgG GdeYWQI ef NdGd GdSWhQ, hSejJgG HYHQI GddHjH HeUQY GdcFjH s
(3BNQgG (B:s
(3hdG RGO ddEfSGf CaVd ef Jbi EPG SGbg fMh GdefjI MGOj hWhHi dYHO bO JfHg WQoag dMGd UdGM ef efGe aSGO s
(3CfTGgG Ydi efhGd QSGdI GdbGVj Ydj Hf YHOGdXGgQs
(3GdeSeGI HeQGJY GdZRdGfs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B29 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1123s
Keywords: (3GdCOHs